2021
DOI: 10.3171/2020.11.jns203567
|View full text |Cite
|
Sign up to set email alerts
|

The Kempe incision for decompressive craniectomy, craniotomy, and cranioplasty in traumatic brain injury and stroke

Abstract: OBJECTIVE Decompressive craniectomy (DC) is an effective, lifesaving option for reducing intracranial pressure (ICP) in traumatic brain injury (TBI), stroke, and other pathologies with elevated ICP. Most DCs are performed via a standard trauma flap shaped like a reverse question mark (RQM), which requires sacrificing the occipital and posterior auricular arteries and can be complicated by wound dehiscence and infections. The Ludwig Kempe hemispherectomy incision (Kempe) entails a T-shaped incision, one limb fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…According to Ordonez-Rubiano [ 17 ], the RQM and Kempe are both effective techniques with comparable risk for scalp necrosis, infection, and cosmetic complications. As noted by Abecassis, the Kempe incision may allow the performance of a larger decompression than the RQM [ 14 ]. When comparing the RQM and Kempe to the RA, Eltabl and colleagues reported that the RA is a safe substitute for these techniques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Ordonez-Rubiano [ 17 ], the RQM and Kempe are both effective techniques with comparable risk for scalp necrosis, infection, and cosmetic complications. As noted by Abecassis, the Kempe incision may allow the performance of a larger decompression than the RQM [ 14 ]. When comparing the RQM and Kempe to the RA, Eltabl and colleagues reported that the RA is a safe substitute for these techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the DHC has also become a routine neurosurgical intervention for malignant cerebral ischemia, aneurysmal subarachnoid hemorrhage, and is under investigation for its efficacy in treating ICH. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the mass effect of the patient’s subdural hematoma and declining mental status, the patient was taken to the operating room for evacuation after her catheter angiogram. We placed the patient in Mayfield skull pins and used a Kempe incision for a large frontotemporoparietal craniotomy [ 9 ]. After elevation of the skull flap, we opened the dura in a stellate fashion, and the subdural hematoma immediately egressed under pressure.…”
Section: Case Presentationmentioning
confidence: 99%